The softening of Chinese digital propaganda: Evidence from the People’s Daily Weibo account during the pandemic - Zhang, Chang; Zhang, Dechun; Shao, Hsuan Lei (Frontiers in Psychology, 2023)
Introduction Social media infuses modern relationships with vitality and brings a series of information dissemination with subjective consciousness. Studies have indicated that official Chinese media channels are transforming their communication style from didactic hard persuasion to softened emotional management in the digital era. However, previous studies have rarely provided valid empirical evidence for the communicational transformation. The study fills the gap by providing a longitudinal time-series analysis to reveal the pattern of communication of Chinese digital Chinese official media from 2019 to 2022. Method The study crawler collected 43,259 posts from the People’s Daily’s Weibo account from 2019 to 2021. The study analyzed the textual data with using trained artificial intelligence models. Results This study explored the practices of the People’s Daily’s Weibo account from 2019 to 2021, COVID-19 is hardly normalized as it is still used as the justification for extraordinary measures in China. This study confirmed that People’s Daily’s Weibo account posts are undergoing softenization transformation, with the use of soft news, positive energy promotion, and the embedding of sentiment. Although the outburst of COVID-19 temporarily increased the media’s use of hard news, it only occur at the initial stage of the pandemic. Emotional posts occupy a nonnegligible amount of the People’s Daily Weibo content. However, the majority of posts are emotionally neutral and contribute to shaping the authoritative image of the party press. Discussion Overall, the People’s Daily has softened their communication style on digital platforms and used emotional mobilization, distraction, and timely information provision to balance the political logic of building an authoritative media agency and the media logic of constructing audience relevance.